Clinical Study and Toxicity Tests of Disclosing Agent Aloe Vera Gel - Said, Fahmi; Rahmawati, Ida; Ningsih, Neny Setiawaty (Asian Journal of Pharmaceutical Research and Development, 2023)
Disclosing agents function to visualize and identify dental plaque on the tooth surface, making it very useful for viewing transparent bacterial plaque for the purposes of oral hygiene instruction, evaluation and research. Aloe vera (Aloe vera) has a unique texture because it is in the form of a gel which has anti-inflammatory, wound healing, antibacterial and anticancer properties. Aloe vera can be developed as a disclosing agent. Clinical trials and toxicity tests can be the basis for the clinical use of aloe vera gel. The purpose of this study was to determine the ability of aloe vera gel as a disclosing agent based on clinical trials and toxicity tests. The research method is by carrying out sample preparation, extraction, gel preparation, clinical trials on human test subjects, and toxicity tests with the BSLT method. Data were analyzed descriptively, linear regression. The test results showed that the average plaque score in formula I (thick gel) was 3.62, while the average plaque score in formula II (less viscous gel) was 2.58. This shows that the more viscous aloe vera gel formula is better than the less viscous aloe vera gel. Based on the test, it is known that the average LC50 value is 2596.88 µg/ml. According to the literature, if the LC50 value is above 1000 µg/ml then the sample does not have a toxic effect.